2011
DOI: 10.1074/jbc.c111.228122
|View full text |Cite
|
Sign up to set email alerts
|

Simplified Bacterial “Pore” Channel Provides Insight into the Assembly, Stability, and Structure of Sodium Channels

Abstract: Eukaryotic sodium channels are important membrane proteins involved in ion permeation, homeostasis, and electrical signaling. They are long, multidomain proteins that do not express well in heterologous systems, and hence, structure/function and biochemical studies on purified sodium channel proteins have been limited. Bacteria produce smaller, homologous tetrameric single domain channels specific for the conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 33 publications
4
48
0
Order By: Relevance
“…Functional studies on wild‐type and mutant prokaryotic channels (Ren et al , 2001; Yue et al , 2002; McCusker et al , 2011; Shaya et al , 2011; Tang et al , 2014) have suggested which regions and residues may be important for ion binding, selectivity and translocation within the SF. However, the detailed locations and environments surrounding the sodium ions within the channels have not been discernable from the crystal structures published to date.…”
Section: Introductionmentioning
confidence: 99%
“…Functional studies on wild‐type and mutant prokaryotic channels (Ren et al , 2001; Yue et al , 2002; McCusker et al , 2011; Shaya et al , 2011; Tang et al , 2014) have suggested which regions and residues may be important for ion binding, selectivity and translocation within the SF. However, the detailed locations and environments surrounding the sodium ions within the channels have not been discernable from the crystal structures published to date.…”
Section: Introductionmentioning
confidence: 99%
“…Rather than having the twenty-four transmembrane segment architecture of eukaryotic Na V s, BacNa V s are built from a six transmembrane segment architecture comprising a VSD and PD (Fig. 1b) that assembles into homotetramers 34; 35; 36; 37; 38; 39 in a manner similar to many voltage-gated potassium channels 1 . Initial studies demonstrated that BacNa V s had an ion selectivity profile that was similar to Na V s 29; 40 , even though the actual selectivity BacNa V selectivity filter sequence has more in common with those from Ca V s than Na V s 29; 33; 41 (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…This aberrant running of full length constructs has also been observed for other orthologues (e.g. NaChBac, NavSp) (Nurani et al, 2008;McCusker et al, 2011).…”
Section: Protein Expression and Purificationmentioning
confidence: 92%